Visual Psychophysics in Head‐Fixed Mice. Issue 1 (26th March 2020) - Krauzlis, Richard J.; Nichols, Nick; Rangarajan, Krsna V.; McAlonan, Kerry; Goldstein, Sheridan; Yochelson, Daniel; Wang, Lupeng
Abstract: We describe a set of protocols for doing visual psychophysical experiments in head‐fixed mice. The goal of this approach was to conduct in mice the same type of precise and well‐controlled tests of visual perception and decision making as is commonly done in primates. For example, these experimental protocols were the basis for our demonstration that mice are capable of visual selective attention in paradigms adapted from classic attention cueing paradigms in primates. Basic Protocol 1 describes how to construct the experimental apparatus, including the removable wheel assembly on which the mice run during the visual tasks, the lick spout used to deliver rewards and detect licks, and the behavioral box that places these components together with the visual displays. We also describe the functions of the computerized control system and the design of the customized head fixture. Basic Protocol 2 describes the preparation of mice for the experiments, including the detailed surgical steps. Basic Protocol 3 describes the transition to a food schedule for the mice and how to operate the experimental apparatus. Basic Protocol 4 outlines the logic of the task design and the steps necessary for training the mice. Finally, Basic Protocol 5 describes how to obtain and analyze the psychometric data. Our methods include several distinctive features, including a custom quick‐release method for holding the head and specific strategies for training mice over multiple weeks. Published 2020. U.S. Government. Basic Protocol 1 : Experimental apparatus Basic Protocol 2 : Head fixture surgery Basic Protocol 3 : General operation of the experimental apparatus Basic Protocol 4 : Behavioral task design and training Basic Protocol 5 : Psychometric data collection and analysis